Answer: (3x+2)(x+4)
Step-by-step explanation:Explanation:
3x2+10x−8
first multiply
3
with −8
and we get −24
then find two numbers that if we add or subtract we get
+10
and if we multiply we get
−24
and the numbers are
+12
and
−2
then we place those numbers as follow :-
3x2+12x−2x−8
then we group them
(3x2+12x)(−2x−8)
now take the common factor out.3x(x+4)−2(x+4)
then group the numbers outside of the brackets
(3x−2)(x+4)
Hey :) it’s (2,5) it’s C !!
4 is the correct answer i believe! :) sorry if wrong.
please put brainliest!
Answer:
x=7
y=-1
Step-by-step explanation:
When the two equations are solved together, they form simultaneous equations.
x+y=6
x-y=8
Let us use the elimination method. if we add the two equations, we eliminate y.
2x=14
x=7
Let us substitute for the value of x obtained above.
x-y=8
7-y=8
y=7-8
y=-1